In-situ and remotely-sensed observations of biomass burning aerosols at Doi Ang Khang, Thailand during 7-SEAS/BASELInE 2015 - Andrew M. Sayer (2018)
© Taiwan Association for Aerosol Research. The spring 2015 deployment of a suite of instrumentation at Doi Ang Khang (DAK) in northwestern Thailand enabled the characterization of air masses containing smoke aerosols from burning predominantly in Myanmar. Aerosol Robotic Network (AERONET) Sun photometer data were used to validate Moderate Resolution Imaging Spectroradiometer (MODIS) Collection 6 ‘Deep Blue’ aerosol optical depth (AOD) retrievals; MODIS Terra and Aqua provided results of similar quality, with correlation coefficients of 0.93–0.94 and similar agreement within expected uncertainties to globalaverage performance. Scattering and absorption measurements were used to compare surface and total column aerosol single scatter albedo (SSA); while the two were well-correlated, and showed consistent positive relationships with moisture (increasing SSA through the season as surface relative humidity and total columnar water vapor increased), insitu surface-level SSA was nevertheless significantly lower by 0.12–0.17. This could be related to vertical heterogeneity and/or instrumental issues. DAK is at ~1,500 m above sea level in heterogeneous terrain, and the resulting strong diurnal variability in planetary boundary layer depth above the site leads to high temporal variability in both surface and column measurements, and acts as a controlling factor to the ratio between surface particulate matter (PM) levels and column AOD. In contrast, while some hygroscopic effects were observed relating to aerosol particle size and Ångström exponent, relative humidity variations appear to be less important for the PM:AOD ratio here.